2019
DOI: 10.5194/isprs-archives-xlii-4-w18-809-2019
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty Modelling of Citizen-Centered Group Decision Making Using Fuzzy-Vikor Case Study: Site Selection of Healthcare Services

Abstract: The participation of citizens in decision-making processes is one of the main concerns in urban planning. People's contributions increase the usability and efficiency of urban facilities. Hospitals and healthcare services are among the most important public facilities that citizens require. This paper aims to improve an approach that could locate the hospitals according to the citizens' preferences. Decision-making process in this situation should consider the uncertainties exist in any steps of decisions-maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The set of criteria, indicated as (c 1 , c 2 , ..., c n ), is used to construct the best-worst method (BWM). Subsequently, the basic model (c b ) is selected and compared with other criteria based on the hourly scale (1)(2)(3)(4)(5)(6)(7)(8)(9). The comparison involves evaluating the basic model with other models, represented as c b = (c b1 , c b2 , ..., c bn ), with c bb = 1, indicating that the minimum basic model (c w ) against others is represented as c w = (c 1w , c 2w , ..., c nw ) and is based on the same scale of measurement.…”
Section: Applying the F-bwm To Assign Weights To The Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…The set of criteria, indicated as (c 1 , c 2 , ..., c n ), is used to construct the best-worst method (BWM). Subsequently, the basic model (c b ) is selected and compared with other criteria based on the hourly scale (1)(2)(3)(4)(5)(6)(7)(8)(9). The comparison involves evaluating the basic model with other models, represented as c b = (c b1 , c b2 , ..., c bn ), with c bb = 1, indicating that the minimum basic model (c w ) against others is represented as c w = (c 1w , c 2w , ..., c nw ) and is based on the same scale of measurement.…”
Section: Applying the F-bwm To Assign Weights To The Criteriamentioning
confidence: 99%
“…Accessibility to health centres and hospitals (HCHs), as defined by the World Health Organization (WHO), refers to the provision of health services that are easily and reasonably available to all segments of both urban and rural populations, with a particular focus on marginalised and underserved groups. The accessibility to HCHs influences the broader aspects of physical, social, and mental well-being and the prevention of preventable mortality [2][3][4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Equity in the use of health care services is an issue, which has increasingly been on the health policy agenda in recent years in both middle-and low-income countries. Distribution of resources within the health care sector may follow many different paths depending on the stated aims or goals of the health system (Mishra et al, 2019;Neisani Samani and Alesheikh, 2019;Whitehead et al, 2019). Utilitarian principles dictate that resources should be allocated in such a way that one can maximize the overall health and wellbeing of society.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that significant differences exist in spatial accessibility to different levels of health care. Neisani Samani and Alesheikh (2019) improved an approach that could identify inequity in health care services based on citizens' preferences. The decision-making process in this situation considered the uncertainties that exist in any steps of decision-making using the Fuzzy-VIKOR method.…”
Section: Introductionmentioning
confidence: 99%